A LITERATURE ANALYSIS OF THE ROLE OF SOCIAL ECONOMIC LAW IN ECONOMIC RESOURCE MANAGEMENT - Loso Judijanto; Muh. Rezky Naim; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
This research aims to analyse the role of social economic law in the management of economic resources based on a review of existing literature. The results of the analysis show that social economic law serves as an important instrument to achieve a balance between economic interests and social justice. Various regulations implemented, such as minimum wage laws, corporate social responsibility (CSR), and environmental licences, ensure that the management of economic resources is conducted in a fair, sustainable, and responsible manner. In addition, public participation and transparency in decision-making processes have proven important in enhancing the legitimacy and accountability of social economy policies. Overall, social economy law plays a crucial role in fairly distributing economic benefits and protecting social welfare and environmental sustainability.